Factors associated with optimized tacrolimus dosing in hematopoietic stem cell transplantation - Butts, Allison R (J Oncol Pharm Pract, 2015)
OBJECTIVE: The primary objective was to analyze the initial tacrolimus concentrations achieved in allogeneic hematopoietic stem cell transplantation patients using the institutional dosing strategy of 1 mg IV daily initiated on day +5. The secondary objectives were to ascertain the tacrolimus dose, days of therapy, and dose changes necessary to achieve a therapeutic concentration, and to identify patient-specific factors that influence therapeutic dose. The relationships between the number of pre-therapeutic days and incidence of graft-versus-host disease and graft failure were delineated. METHODS: A retrospective chart review included adult allogeneic hematopoietic stem cell patients who received tacrolimus for graft-versus-host disease prophylaxis in 2012. Descriptive statistics, linear and logistic regression, and graphical analyses were utilized. RESULTS: Ninety-nine patients met the inclusion criteria. The first concentration was subtherapeutic (<10 ng/ml) in 97 patients (98%). The median number of days of tacrolimus needed to achieve a therapeutic trough was 10 with a median of two dose changes. The median therapeutic dose was 1.6 mg IV daily. Approximately 75% of patients became therapeutic on ≤2 mg IV tacrolimus daily. No relationship was found between therapeutic dose and any patient-specific factor tested, including weight. No relationship was found between the number of days of therapy required to achieve a therapeutic trough and incidence of graft-versus-host disease or graft failure. CONCLUSION: An initial flat tacrolimus dose of 1 mg IV daily is a suboptimal approach to achieve therapeutic levels at this institution. A dose of 1.6 mg or 2 mg IV daily is a reasonable alternative to the current institutional practice.